TEKNOLOGI DAUR ULANG KERTAS KORAN MENJADI KERAJINAN TANGAN BERNILAI JUAL TINGGI DAN ANALISA KELAYAKANNYA (Studi Kasus Di Kelompok Ibu Rumah Tangga Sekarwangi Malang) - Eri Yusnita Arvianti; Karunia Setyowati Suroto; Tourusman Situmeang (Universitas Tribhuwana Tunggadewi, 2016)
Trash from the newspaper is something that is often overlooked and considered one eye by some people. Midden in down-town city often do not immediately handled well. In fact, if utilized will bring value to the efforts to find a distinct advantage. Garbage such as old newspapers, cardboard and garbage that comes from the dried leaves can be recycled into craft high value such as bags, photo frames, mirror frames, tissue box, blocnotes. This study aims to look at the benefits, costs and feasibility of the business of recycling newsprint. This event was held at the business group Sekarwangi from April to November 2016.The method applied is a method of collecting primary and secondary data. A set of analysis applied to answer this purpose, such as total cost, total revenue and net BC ratio. The analysis showed that the amount of the costs and benefits of newsprint recycling efforts have amounted Rp 46.612.400, - and Rp. 82.500.000, -, and this business is viable with the BC ratio of 1.77. Through the application of good management in marketing and finance will take this business as a promising business venture because it can help in increasing the family income.